The Javanese Hegemony in Cambodia for 120 Years (682-802) - Setiawan, Martin Darma (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This paper explores historical and geopolitical relations between 9th-century Java and Khmer, with a focus on the Sdok Kak Thom inscription. discusses pre-Angkor Southeast Asia's socio-cultural landscape, including Chenla-Kamboja culture and Sriwijaya Thalassocrazy, using colonization and cultural trade theories to analyze dynamics among Java, Sriwijaya, and Cambodia. This study employs a multidisciplinary method approach to examine Java-Khmer relations in the 9th century. It integrates historical analysis, archaeological investigation, textual interpretation, theoretical frameworks, and comparative analysis. The results of this research suggest three divisions within the Sriwijaya Kingdom: Kedatuan, Samaryyada, and Mandala, which served trade, political, and spiritual purposes. It examines temple construction during the Mataram-Sriwijaya period in Java, with emphasis on the role of the Kalang people, their significance in the varna system, and Austronesian social stratification. This article also involves Sriwijaya's involvement in temple construction and maritime expeditions, encouraging the importation of enabled workers. He concluded that temple construction in Java likely involved rapid mobility of activated workers, facilitated by Sriwijaya activities and partnerships, with the Kalang community playing a significant role.